2008
DOI: 10.3168/jds.2007-0603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Free-Stall Mattress Bedding Treatments to Reduce Mastitis Bacterial Growth

Abstract: Bacterial counts were compared in free-stall mattresses and teat ends exposed to 5 treatments in a factorial study design on 1 dairy farm. Mattresses in five 30-cow groups were subjected to 1 of 5 bedding treatments every other day: 0.5 kg of hydrated limestone, 120 mL of commercial acidic conditioner, 1 kg of coal fly ash, 1 kg of kiln-dried wood shavings, and control (no bedding). Counts of coliforms, Klebsiella spp., Escherichia coli, and Streptococcus spp. were lowest on mattresses bedded with lime. Mattre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 11 publications
1
26
0
2
Order By: Relevance
“…Both alkaline and acidic conditioners have been used successfully to modify coliform and streptococcal counts on cow mattresses (Kristula et al., ) and in sawdust (Paduch, Mohr, & Krömker, ; Proietto et al., ). When using lime, both positive and negative effects were observed at teat level, that is, a reduction of bacterial counts as well as damage to teat skin (Kristula et al., ; Paduch et al., ). With acidifiers, neither positive nor negative effects were observed (Kristula et al., ; Proietto et al., ).…”
Section: Prevention Detection and Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Both alkaline and acidic conditioners have been used successfully to modify coliform and streptococcal counts on cow mattresses (Kristula et al., ) and in sawdust (Paduch, Mohr, & Krömker, ; Proietto et al., ). When using lime, both positive and negative effects were observed at teat level, that is, a reduction of bacterial counts as well as damage to teat skin (Kristula et al., ; Paduch et al., ). With acidifiers, neither positive nor negative effects were observed (Kristula et al., ; Proietto et al., ).…”
Section: Prevention Detection and Controlmentioning
confidence: 99%
“…When using lime, both positive and negative effects were observed at teat level, that is, a reduction of bacterial counts as well as damage to teat skin (Kristula et al., ; Paduch et al., ). With acidifiers, neither positive nor negative effects were observed (Kristula et al., ; Proietto et al., ). The effect of acidifiers is time‐limited.…”
Section: Prevention Detection and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of Klebsiella spp. is also observed on mattresses without shavings or other bedding (Kristula et al, 2008). In recent years, Klebsiella spp.…”
Section: Introductionmentioning
confidence: 97%
“…However, the parasite is resistant to all commonly used chemical disinfectants, making it particularly difficult to control (Fayer, 2008). Hydrated lime, or calcium hydroxide, can be used to sanitise animal facilities from bacteria and viruses (Kristula et al, 2008;Anonymous, 2009). It has been shown that hydrated lime decreases the viability of C. parvum in the laboratory (Zintl et al, 2010), and when hydrated lime disinfection of the calf pens was used as a complement to the standard cleaning procedures in two Swedish herds with long-lasting cryptosporidiosis problems, the farmers reported a lower incidence and less severe diarrhea in the calves (C. Axén personal communication).…”
Section: Introductionmentioning
confidence: 99%